SketchUp 4.0. - Smith, Lee Anne (Architectural Record, 2004)
This article presents information on the latest version of the popular and reasonably priced 3D sketching tool, SketchUp 4.0. New features in this release include one called "Follow Me" that allows users to extrude or push a surface along a known path; "The Intersector," which lets designers connect and intersect different 3D shapes with a single mouse click; a "Texture Tweaker," in which photographs or textures can be overlaid and stretched along continuous 2D or 3D surfaces; and a new scripting interface for advanced users.